2017
DOI: 10.1002/anie.201609395
|View full text |Cite
|
Sign up to set email alerts
|

Peptide N‐Amination Supports β‐Sheet Conformations

Abstract: The conformational heterogeneity of backbone N-substituted peptides limits their ability to adopt stable secondary structures. Herein, we describe a practical synthesis of backbone aminated peptides that readily adopt β-sheet folds. Data derived from model N-amino peptides suggest that extended conformations are stabilized through cooperative steric, electrostatic, and hydrogen-bonding interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…We previously showed that Boc-protected hydrazino acids can be chemoselectively condensed with amines at their C-termini without protection of N. 17 The N-terminus can then be acylated with a variety of protected amino acid chlorides to provide backbone aminated peptide derivatives.…”
Section: Letter Synlettmentioning
confidence: 99%
“…We previously showed that Boc-protected hydrazino acids can be chemoselectively condensed with amines at their C-termini without protection of N. 17 The N-terminus can then be acylated with a variety of protected amino acid chlorides to provide backbone aminated peptide derivatives.…”
Section: Letter Synlettmentioning
confidence: 99%
“…The smallest β‐sheet template reported to date involves the use of N‐aminated amino acids to replace the C5 hydrogen bond . Applied to the model β‐hairpin GB1 at non‐hydrogen bonding positions, this strategy preserves all side chains for molecular recognition but has not been used in such applications yet.…”
Section: β‐Sheet Peptide Mimeticsmentioning
confidence: 99%
“…47,48 We recently described an approach to β-strand stabilization based on peptide backbone N-amination (Figure 1C). 42 The conformational and non-aggregating characteristics of N-amino peptides (NAPs) are consistent across distinct models of βsheet folding and are attributed to cooperative non-covalent interactions involving the Nα-NH 2 substituent. These qualities distinguish NAPs from N-alkylated peptides that do not readily adopt or stabilize β-strand conformations.…”
Section: ■ Introductionmentioning
confidence: 99%